Efektifitas Bimbingan Kelompok Berbasis Online dengan Menggunakan Metode Diskusi dalam Meningkatkan Rasa Percaya Diri - Nike Gusmida; Fitria Kasih; Fuaddillah Putra (Journal on Education, 2023)
This research entitled “The Online-Based Group Guidance Effectiveness Using Discussion Method in Increasing Self-Confidence”. The purpose of this research is to describe: an overview of the student self-confidence before and after participating online-based group guidance using the discussion method, as well as the online-based group guidance effectiveness using the discussion method in increasing student self-confidence. This is a experimental research. The population of this research was 10 students using purposive sampling technique. The instrument was questionnaire, while the data analysis used interval data with t-test, as well as the results of the pretest and the posttest. The results of this research: 1) The description of students self-confidence before participating online-based group guidance using the discussion method is in a fairly high category 2) The description of students self-confidence after participating online-based group guidance using the discussion method is in the low category. 3) There is an effectiveness of online-based group guidance using the discussion method in increasing students self-confidence. It is recommended for counseling teachers in order to take the advantage of technological media in providing counseling guidance. By providing online-based group guidance using the discussion method with the zoom application, students will get new innovations.